Analisis Alat Bantu Tuning Fisikal Basis Data pada Sql Server 2008 - Marlene Martani; Hanny Juwitasary; Arya Nata Gani Putra (Bina Nusantara University, 2014)
Nowadays every company has been faced with a business competition that requires the company to survive and be superior to its competitors. One strategy used by many companies is to use information technology to run their business processes. The use of information technology would require a storage which commonly referred to as a database to store and process data into useful information for the company. However, it was found that the greater the amount of data in the database, then the speed of the resulting process will decrease because the time needed to access the data will be much longer. The long process of data can cause a decrease in the company’s performance and the length of time needed to make decisions so that this can be a challenge to achieve the company’s competitive advantage. In this study performed an analysis of technique to improve the performance of the database system used by the company to perform tuning on SQL Server 2008 database physically. The purpose of this study is to improve the performance of the database used by speeding up the time it takes when doing query processing. The research methodology used was the method of analysis such as literature studies, analysis of the process and the workings of tuning tools that already exist in SQL Server 2008, and evaluation of applications that have been created, and also tuning methods that include query optimization and create index. The results obtained from this study is an evaluation of the physical application tuning tools that can integrate database functionality of other tuning tools such as SQL Profiler and Database Tuning Advisor.